2020
DOI: 10.1186/s12883-020-01747-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an increased prevalence of multiple sclerosis: a population-based study of Tehran registry during 1999–2018

Abstract: Background: The epidemiological characteristics of multiple sclerosis (MS) have been investigated in various studies, which have revealed that the prevalence of MS varies across countries. The present study was conducted to investigate the longitudinal prevalence of MS in Tehran, Iran. Methods: The present population-based study was conducted in Tehran, the capital of Iran from 1999 to 2018 based on the annual report data provided by the Iranian MS Society (IMSS) registry system. The age-standardized and crude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Multiple sclerosis (MS) with an age-adjusted prevalence of 137.6 and incidence of 6.7 per 100000 is a common neurologic disease in Iran ( Almasi-Hashiani et al, 2020 ; Hosseinzadeh et al, 2019 ). A recent systematic review showed high and rising prevalence in the country ( Azami et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) with an age-adjusted prevalence of 137.6 and incidence of 6.7 per 100000 is a common neurologic disease in Iran ( Almasi-Hashiani et al, 2020 ; Hosseinzadeh et al, 2019 ). A recent systematic review showed high and rising prevalence in the country ( Azami et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The disease usually occurs at the age of 20-50 and is about 3 times more common among women than men [ 4 ]. The prevalence of MS in Iran has also increased significantly in recent years, reaching from 73.7 per 100,000 in 2006 to 137.6 per 100,000 in 2018 [ 5 ]. According to the studies carried out from 2011 to 2020 in different provinces, the prevalence of the disease in Iran ranged from 27.7 per 100,000 in East Azerbaijan to 148.06 per 100,000 in Tehran [ 6 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that Multiple Sclerosis (MS) prevalence has been rising in Iran in the recent years [1] . Immune system modulation or suppression is the key approach in MS treatment modalities.…”
Section: Introductionmentioning
confidence: 99%